Households’ Non-leisure Time Allocation for Children and Determinants of Child Labour in Punjab, Pakistan (The Pakistan Development Review, 1998)
Pakistan is one of those countries in Asia where incidence of child labour is very high. Children should not have to work, but the estimates of the Child Labour Survey 1996 show that there are 3.3 million working children between the ages of 5-14 years in Pakistan. Due to political, social and economic pressures, developing countries like Pakistan tend to react by enacting legislation which bans child labour. Countries which are now developed did the same thing when they successfully completed their industrialisation. Child labour is often harmful for the children, but there are situations where the alternatives to child labour may offer only deeper poverty both for the children and their families. Therefore, mishandling of this issue can make matters from bad to worse, for example, if legislation pushes children into even worse situations. The Government of Pakistan has enacted the Employment of Children Act of 1991 which has banned employment of children below the age of 14 years and their employment is now a cognisable offence under the Act punishable by imprisonment and fine.1 Such interventions can lead to reductions in the already limited choices available to the child. For example, this legislation may mean that the child can neither work nor go to school. To put it differently, this ban does not address market failures, for example, in the education market.